Asymptotic Distribution of the Number for Error in the Time of Random Observation - Lu Chuanlai (Tongxin xuebao)
In this paper, it is discussed that the distribution of sum for errors in the random time of observation is approached to a normal distribution, when the sequence X1 of errors in an unit time is a m-dependent.